Peran Ulama dan Intelektual Muslim dalam Transformasi Sosial Masyarakat Muslim Modern - Muhlis Abdul Karim; Fatimah Zahra Natsir; Ismail Hasan Waerata (Al-Jinan : Jurnal Studi Islam, 2026)
The role of ulama and Muslim intellectuals in the social transformation of modern Muslim society is increasingly complex amid the challenges of globalization and digitalization. This study aims to analyze the forms and patterns of ulama and Muslim intellectual contributions to social change in Indonesia. Using qualitative research with a case study approach, data were collected through in-depth interviews, observation, and documentation. Results indicate that ulama and Muslim intellectuals exercise influence through four main channels: religious education, fatwa institutions, social organizations, and digital media. The study concludes that contemporary ulama and Muslim intellectuals must integrate classical Islamic scholarship with critical social sciences to remain relevant as agents of social transformation in an era of rapid change.